Preparation and application method of functional oligomer based on oxidative cracking of retired polyolefin
By introducing aerobic oxidation catalyst and oxidant gas into the decommissioned polyolefin, the β-fracture reaction of the polyolefin is achieved, functionalized oligomers are obtained, and dynamic cross-linking reaction with epoxy rubber is carried out, which solves the separation of oxidative cracking products and high-quality oxidation cracking products The problem of value utilization has achieved efficient resource recycling and environmentally friendly material preparation.
Patent Information
- Application Number
- CN202411466942.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-21
AI Technical Summary
The existing oxidation and cracking technology is difficult to effectively avoid the subsequent separation of products, and high value utilization is difficult to achieve, resulting in waste of resources and environmental pollution.
Carbon and oxygen radicals are introduced into the decommissioned polyolefin chain by aerobic oxidation organic catalyst and oxidant gas, and the chain break of the decommissioned polyolefin is achieved through the β-break reaction of the free radicals, and functionalized oligomers in the form of semi-crystalline polymer are obtained. , and use it to dynamically cross-link with epoxy rubber to prepare elastomeric materials.
Low-temperature controlled oxidation and cracking of retired polyolefins is achieved, and the molecular weight, molecular weight distribution and functional degree of the product are adjustable, avoiding the difficulty of subsequent separation, and an elastomeric material with excellent mechanical properties and thermomechanical properties is directly constructed.
Smart Images

Figure CN119391047A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of retired polyolefin recovery, and in particular to a preparation and application method of a functionalized oligomer based on oxidative cracking of retired polyolefin. Background Art
[0002] Since the invention of plastics in the early 20th century, as the most important synthetic polymer material in daily life, the annual output has continued to grow from 2 million tons in 1950 to more than 390 million tons in 2021. As of 2021, only 11% of the 8.7 billion tons of waste plastics produced worldwide have been recycled. According to the current waste plastic management methods, it is estimated that by 2050, 12 billion tons of waste plastics will be buried or flow into the natural environment. Improper disposal of retired plastics has caused serious "white" pollution and "microplastic" problems.
[0003] In order to solve the pollution problem of waste plastics, people often choose to incinerate or bury waste plastics, which will cause serious waste of resources and secondary pollution to the soil, water environment and atmosphere. Obviously, these two methods are unpopular in the plastic circular economy. Physical recycling of sorted waste plastics is a simple, economical and effective way to deal with large-scale waste plastics, but it is limited by the deterioration of material properties after multiple recycling and cannot achieve recycling in the true sense of circular economy; chemical recycling of depolymerization into monomers or oligomers is an effective alternative. The obtained monomers or oligomers can be repolymerized into raw materials or new materials to achieve circular economy.
[0004] In the chemical recovery of retired polyolefins, in addition to methods such as pyrolysis, catalytic cracking, tandem hydrogenolysis aromatization, and cross-alkane metathesis, oxidative cracking is an effective alternative. Oxidative cracking can achieve chain scission of retired polyolefins at low temperatures, while introducing some valuable reactive groups, such as hydroxyl, carbonyl, and carboxyl groups, to achieve the added value of the cracking products. At present, a variety of oxidative cracking systems have been developed. Commonly used oxidants include O2, NO, NO2, HNO3, and H2O2. The products are mostly mixtures of short-chain dicarboxylic acids. The wide distribution of mixed products and low selectivity of high-value products bring difficulties to subsequent separation and utilization. Therefore, how to avoid the subsequent separation of oxidative cracking products and achieve high-value utilization of products is still a difficult problem. Summary of the invention
[0005] The purpose of the present invention is to provide a preparation and application method of a functionalized oligomer based on oxidative cracking of retired polyolefins, wherein carbon and oxygen free radicals are introduced into the retired polyolefin chain by an aerobic oxidation organic catalyst and an oxidant gas, and the chain scission of the retired polyolefin is achieved by a β-fragmentation reaction of the free radicals to obtain a functionalized oligomer in the form of a semi-crystalline polymer, and the functionalized oligomer can be directly used to undergo a dynamic crosslinking reaction with epoxy rubber to prepare an elastomeric material.
[0006] To achieve the above objectives, the present technical solution provides a method for preparing a functionalized oligomer based on oxidative cracking of retired polyolefins, comprising the following steps:
[0007] dissolving an aerobic oxidation catalyst and retired polyolefin in an organic solvent at a certain mass ratio and transferring the dissolved catalyst and retired polyolefin into a reactor;
[0008] An oxidant gas is introduced into the reactor until it is sealed, the reaction temperature of the reactor is adjusted to a high temperature state, and the reaction is stirred for a period of time to obtain a precipitated material, wherein the oxidant gas and the retired polyolefin undergo a free radical oxidation reaction under the action of an aerobic oxidation catalyst to generate free radicals, and the free radicals are used to break the retired polyolefin and introduce functional groups;
[0009] The precipitation material is dissolved to obtain a reaction precipitation solution, the reaction precipitation solution is filtered to obtain a precipitation solid, and the precipitation solid is dried to obtain a functionalized oligomer.
[0010] This scheme is to use aerobic oxidation organic catalysts and oxidant gases to introduce carbon free radicals, peroxy free radicals, and oxygen free radicals into the retired polyolefin chain, and achieve chain scission of the retired polyolefin through the β-scission reaction of the free radicals to obtain functionalized oligomers with reduced molecular weight. At the same time, the oxygen free radicals can be further derived into oxidized groups such as carbonyl, carboxyl, and hydroxyl. By precisely controlling the reaction conditions to control the cumulative degree of β-scission events of the free radicals, the molecular weight, molecular weight distribution and functionality of the cleavage products can be adjusted, thereby obtaining functionalized oligomers that meet the requirements.
[0011] Further, the aerobic oxidation catalyst is selected from one or more of N-hydroxyphthalimide, N-hydroxysuccinimide, N-hydroxymaleimide, N-acetylphthalimide, 3,4,5,6-tetrachloro-N-hydroxyphthalimide, 3,4,5,6-tetrabromo-N-hydroxyphthalimide, 3,4,5,6-tetrafluoro-N-hydroxyphthalimide, 2,2,6,6-tetramethylpiperidinoxide, N,N'-dihydroxyphthalimide, N,N',N"-trihydroxyisocyanuric acid, 2-azaadamantane-N-oxide, N-hydroxy-3,4,5,6-tetraphenylphthalimide, N,N'-dihydroxypyromellitic acid imide, and N-hydroxyquinoline imide, and mixed in any proportion.
[0012] It should be noted that the aerobic oxidation catalyst catalyzes and accelerates the aerobic oxidation reaction between the oxidant and the retired polyolefin to produce a series of free radicals, including carbon free radicals, oxygen free radicals and peroxyl free radicals, wherein the free radicals undergo a β-chain scission reaction with the retired polyolefin to obtain oligomers with reduced molecular weight, while the oxygen free radicals and peroxyl free radicals undergo oxidation and transfer termination reactions to derive into oxidized groups such as carbonyl, carboxyl, and hydroxyl.
[0013] Furthermore, the retired polyolefin is one or more of low-density polyethylene, high-density polyethylene, linear low-density polyethylene, isotactic polypropylene, syndiotactic polypropylene, random polypropylene, polystyrene, ethylene and α-olefin copolymers mixed in any proportion.
[0014] Furthermore, the mass ratio of the aerobic oxidation catalyst to the retired polyolefin is 1 to 100: 100 to 1. Generally speaking, the content of the aerobic oxidation catalyst is inversely proportional to the molecular weight of the functionalized oligomer and is directly proportional to the derivatization of the functional group. In this scheme, the molecular weight, molecular weight distribution and functionality of the functionalized oligomer can be regulated by regulating the content of the aerobic oxidation catalyst.
[0015] Furthermore, the organic solvent is selected from any one or a mixture of any two or more of 1,1,2,2-tetrachloroethane, 1,2-dichloroethane, chloroform, toluene, xylene, o-dichlorobenzene, 1,2,4-trichlorobenzene, tetralin, n-butyl acetate, and straight-chain alkanes, isoalkanes, and cycloalkanes having 4 to 10 carbon atoms.
[0016] Furthermore, in this scheme, a certain mass ratio of aerobic oxidation catalyst and retired polyolefin can be mixed and then transferred to the reactor and then an organic solvent can be added to the reactor. Alternatively, a certain mass ratio of aerobic oxidation catalyst and retired polyolefin can be directly dissolved in an organic solvent and then transferred to the reactor together.
[0017] Furthermore, the oxidant gas is one or more of air, oxygen, ozone, nitrogen dioxide, and nitric oxide mixed in any proportion.
[0018] Furthermore, the pressure of the oxidant gas is 1 to 30 bar. Generally speaking, the concentration of the oxidant gas is inversely proportional to the molecular weight of the functionalized oligomer and is directly proportional to the derivatization of the functional group. In this scheme, the molecular weight, molecular weight distribution and functionality of the functionalized oligomer can be regulated by regulating the concentration of the oxidant gas.
[0019] Furthermore, the oxidant gas is introduced into the reactor by continuous ventilation or gas replacement until it is sealed.
[0020] Furthermore, when the oxidant gas is introduced into the reactor by gas replacement until it is sealed, the reactor is repeatedly evacuated and replaced by nitrogen for multiple times, and then the reactor is evacuated and replaced by the oxidant for multiple times to achieve a sealed state. Preferably, the reactor can be repeatedly evacuated and replaced by nitrogen for five times, and then evacuated and replaced by the oxidant gas for three times to achieve a sealed state.
[0021] Furthermore, the reaction temperature of the reactor is regulated to 90°C to 130°C, and the reaction is stirred for 1h to 48h. Generally speaking, the longer the reaction time, the more accumulated β-fracture events, which is reflected in the lower molecular weight of the functionalized oligomer; similarly, the functionality will increase with the increase of reaction time. In other words, the reaction temperature and reaction time are inversely proportional to the molecular weight of the functionalized oligomer and directly proportional to the functionality. This scheme can regulate the molecular weight, molecular weight distribution and functionality of the functionalized oligomer by regulating the reaction temperature and reaction time.
[0022] Furthermore, the oxidant gas and the retired polyolefin undergo a free radical oxidation reaction under the action of an aerobic oxidation catalyst to produce carbon free radicals, oxygen free radicals and peroxy free radicals, and the functional groups are one or more of carboxyl groups, hydroxyl groups, carbonyl groups, ester bonds, peroxy groups, epoxy groups, ether bonds, peroxy acid groups, nitro groups, and sulfonic acid groups mixed in any proportion.
[0023] Further, the reaction precipitation solution is obtained by dissolving the precipitation material with methanol solvent, the reaction precipitation solution is filtered to obtain a precipitated solid, and the precipitated solid is vacuum dried at 65° C. to 80° C. for 10 to 15 hours to obtain a functionalized oligomer. Preferably, the substrate solid is vacuum dried at 70° C. for 12 hours.
[0024] Furthermore, the functionalized oligomers prepared in this scheme have a number average molecular weight of 1500-10000Da, a molecular weight distribution index of 2.0-4.0, a crystallinity of 30-60%, a functionality of 0.5-6.0 mol% (relative to ethylene monomer) compared to ethylene monomer, and a functional group selectivity of 0-50%.
[0025] As described above, the present scheme provides a method for preparing functionalized oligomers based on oxidative cracking of retired polyolefins. By precisely controlling the reaction conditions (oxidant concentration, catalyst dosage, reaction time), the cumulative degree of β-fragmentation events of free radicals is controlled to achieve adjustable molecular weight, molecular weight distribution and functionality of the cracking products. The functionalized oligomers with different functionalities and molecular weights obtained in this scheme may have different application scenarios. For example, functionalized oligomers with larger molecular weights can be used as processing aids, and functionalized oligomers with smaller molecular weights can be used to construct elastomeric materials.
[0026] Specifically, since the functionalized oligomer constructed in this scheme is a semi-crystalline polymer, the elastomeric material can be prepared by directly utilizing the reactive activity of the oxidative groups in the functionalized oligomer to undergo a dynamic crosslinking reaction with epoxy rubber without separation. Correspondingly, in a second aspect, this scheme provides an application method of the functionalized oligomer based on oxidative cracking of retired polyolefins, comprising the following steps:
[0027] Mixing epoxidized rubber, functionalized oligomer and catalyst in a certain mass ratio to obtain a mixture, and premixing the mixture in an organic solvent and stirring and reacting it at high temperature for a period of time, wherein the functionalized oligomer is prepared according to the preparation method of the functionalized oligomer based on oxidative cracking of retired polyolefins according to the first aspect;
[0028] The organic solvent is removed to obtain a solid mixture, and the solid mixture is placed on a flat vulcanizer to undergo a vulcanization and cross-linking reaction to obtain an elastomeric material.
[0029] It should be noted that, due to the presence of oxidized groups on the functionalized oligomer, the oxidized groups on the functionalized oligomer and the epoxy groups of the epoxidized rubber can react under the action of a catalyst to generate new bonds and new groups to produce a cross-linked network, thereby constructing an elastomeric material, wherein the new bonds and new groups in the cross-linked network are dynamic chemical cross-linking points, and the semi-crystalline locations on the functionalized oligomer are physical cross-linking points. In other words, the functional groups of the functionalized oligomer and the epoxy groups of the epoxidized rubber undergo a cross-linking reaction to obtain an elastomeric material, and the cross-linked network of the elastomeric material has both dynamic chemical cross-linking points and physical cross-linking points.
[0030] Furthermore, the epoxidized rubber is one or more of epoxidized butadiene rubber, epoxidized natural rubber, epoxidized polyisoprene rubber, epoxidized styrene-butadiene rubber, epoxidized butyl rubber, epoxidized chloroprene rubber, epoxidized ethylene-propylene-diene rubber, and epoxidized styrene-butadiene-styrene block copolymer, mixed in any proportion.
[0031] Further, the epoxidized rubber has an epoxidation rate of 1% to 50%.
[0032] Furthermore, the catalyst is an esterification catalyst or an ester exchange catalyst, selected from zinc acetate, zinc acetylacetonate, 2-ethylhexanoate tin, dibutyltin dilaurate, dibutyltin diacetate, dibutyltin diacetylacetonate, 1,2-dimethylimidazole, 1-methylimidazole, 2-ethyl-4-methylimidazole, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1,8-diazabicyclo[5.4.0]undec-7-ene, 1,4-diazabicyclo[2.2.2]octane, triphenylphosphine, triethanolamine, benzyldimethylamine, or one or more thereof, mixed in any proportion.
[0033] Furthermore, the mass ratio of the epoxidized rubber, the functionalized oligomer and the catalyst is 1:0.02:0.03 to 1:1:0.03. The advantage of such control is that the content of the crystalline phase in the elastomer material can be controlled by adjusting the amount of the functionalized oligomer, thereby achieving a coordinated balance between the elasticity of the amorphous phase and the strength of the crystalline phase.
[0034] Furthermore, the organic solvent is any one of 1,1,2,2-tetrachloroethane, 1,2-dichloroethane, chloroform, toluene, xylene, o-dichlorobenzene, 1,2,4-trichlorobenzene, tetralin, n-butyl acetate, and straight-chain alkanes, isoalkanes, and cycloalkanes having 4 to 10 carbon atoms, or a mixture of any two or more thereof.
[0035] Further, the mixture is premixed in an organic solvent and stirred at 85°C to 100°C for 10 to 30 minutes, wherein the stirring speed is 400 to 600 rpm. Preferably, the mixture is premixed in an organic solvent and stirred at 90°C for 15 minutes, wherein the stirring speed is 500 rpm.
[0036] Further, the solid mixture is placed on a flat vulcanizer to undergo a vulcanization crosslinking reaction to obtain an elastomeric material, wherein the vulcanization reaction conditions are: a vulcanization temperature of 130°C to 160°C, a vulcanization pressure of 8 to 12 MPa, and a vulcanization time of 25 to 40 minutes. Preferably, the vulcanization reaction conditions are a vulcanization temperature of 150°C, a vulcanization pressure of 10 MPa, and a vulcanization time of 30 minutes.
[0037] Furthermore, the cross-linked network of the elastomeric material prepared by the present scheme has dynamic chemical cross-linking points and physical cross-linking points, wherein the dynamic chemical cross-linking points are provided by new bonds and new groups generated by the reaction of the oxidized groups of the functionalized oligomers with the epoxy groups in the epoxidized rubber, and the physical cross-linking points are provided by the semi-crystalline regions of the functionalized oligomers.
[0038] Compared with the prior art, this technical solution has the following characteristics and beneficial effects:
[0039] This scheme provides a method for preparing functionalized oligomers based on oxidative cracking of retired polyolefins, wherein a large number of free radicals are generated through free radical oxidation reaction, wherein some free radicals break the polyolefin chains to obtain cracking products of different molecular weights, and at the same time, free radicals are oxidized to form functional groups including oxidized groups, and by controlling the cumulative degree of β-fragmentation events of free radicals, the molecular weight, molecular weight distribution and functionality of the cracking products can be adjusted, thereby obtaining functionalized oligomers with controllable molecular weight and functionality. Since the functionalized oligomers of this scheme are semi-crystalline polymers, the reactivity of the oxidized groups on the chain can be directly utilized to undergo dynamic crosslinking reaction with epoxy rubber without separation to prepare elastomeric materials.
[0040] In other words, this scheme proposes for the first time a method for the preparation and application of functionalized oligomers based on oxidative cracking of retired polyolefins. By using aerobic oxidation organic catalysts, low-temperature controllable oxidative cracking of retired polyolefins is achieved, and the molecular weight, molecular weight distribution and degree of functionalization of the cracking products are adjustable. Without subsequent separation, the reaction characteristics of the product are directly used to construct an elastomeric material with excellent mechanical and thermomechanical properties, avoiding the previous problems of difficulty in separating and reusing oxidative cracking products. This scheme proposes a new, simple and effective high-value recycling route for retired polyolefins, which has guiding significance for subsequent research and is conducive to the green and sustainable development of polymer engineering. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 is a reaction equation for preparing a functionalized oligomer according to an embodiment of the present invention.
[0042] Figure 2 is a molecular weight distribution diagram of a functionalized oligomer according to an embodiment of the present invention.
[0043] Figure 3 It is the stress-strain curve of elastic material.
[0044] Figure 4 It is a graph showing the storage modulus changing with temperature. DETAILED DESCRIPTION
[0045] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.
[0046] The present invention provides a preparation and application method of a functionalized oligomer based on oxidative cracking of retired polyolefins. In order to make the purpose, technical scheme and effect of the present invention clearer, the present invention is further described in detail below. It should be understood that the specific implementation described herein is only used to explain the present invention and is not intended to limit the present invention.
[0047] 1. Performance test description:
[0048] The molecular weight of the polymer (M w and M n ) and its distribution index High temperature gel permeation chromatography (PL-GPC220) was used for determination. 1,2,4-trichlorobenzene was used as solvent to prepare a 0.1-0.3wt.% polymer solution at 150°C. Polystyrene with narrow molecular weight distribution was used as standard sample and measured at 150°C. The solvent flow rate was 1.0mL / min. The parameter k=5.91×10 -4 , α=0.69.
[0049] Melting point of functionalized oligomer (T m ) and glass transition temperature (T g ) was measured by TA Instruments Q2500. Take 5.0-8.0 mg of polymer sample and heat it to 190°C at 30°C / min, keep it constant for 5 minutes to eliminate the thermal history, then cool it to -120°C at 10°C / min, keep it constant for 3 minutes, and then heat it to 190°C at 10°C / min. The melting point and glass transition temperature of the polymer are obtained from the second heating curve.
[0050] The functionality of the functionalized oligomers and the relative content of each oxidized group were determined using high temperature H-NMR spectroscopy ( 1 H NMR) was measured at 130°C, using a Bruker AC 400. The polymer was prepared into a 10% by mass deuterated o-dichlorobenzene solution at 150°C and pre-dissolved for 3-4 hours to make the sample solution uniform.
[0051] Mechanical properties tests were performed using a universal testing machine (Instron 3345) in accordance with ASTM-D412, equipped with a 500N electronic load cell and mechanical fixtures. The test temperature was 25°C, and the upper crossbeam movement speed was 50 mm / min. The reprocessing procedure was to cut the material into small pieces of about 0.5 cm and then hot press at 160°C for 1 h. The reprocessing efficiency was defined as (tensile toughness after reprocessing / tensile toughness before reprocessing) × 100%.
[0052] The gel content was determined by Soxhlet extraction, where the material was extracted in toluene at 120°C for 8 h and then dried under vacuum. The gel content was defined as (sample weight after extraction / sample weight before extraction) × 100%.
[0053] The thermomechanical properties test was carried out on a dynamic mechanical analyzer TA Q800 using rectangular specimens (20 mm × 5 mm × 0.3 mm) with a heating range of −120–180 °C, a rate of 3 °C / min, a constant force of 0.01 N, and a frequency of 1 Hz.
[0054] 2. Design of implementation example:
[0055] Example 1
[0056] In this embodiment, the retired polyolefin is selected as high-density polyethylene (M w =18.6 kDa, ), the aerobic oxidation organic catalyst is N-hydroxyphthalimide, the solvent is 1,1,2,2-tetrachloroethane, the oxidant gas is oxygen, and the oxidant gas injection method is gas replacement. Before the experiment, high-density polyethylene and N-hydroxyphthalimide are mixed in a ratio of 10:2 and placed in a reactor. The solvent 1,1,2,2-tetrachloroethane is added to the reactor to maintain the overall concentration at 0.1g / ml. After the reactor was repeatedly evacuated and replaced with nitrogen five times, it was evacuated and replaced with oxygen three times to seal the entire reactor. The temperature of the reactor was raised to 110°C, and the stirring was turned on to 300 rpm. The reaction was stopped after 1 hour of reaction. The reacted material was precipitated in a large amount of methanol, stirred overnight, and filtered to obtain a solid, which was then vacuum dried at 70°C for more than 12 hours to obtain a functionalized oligomer. All materials used in the experiment were used directly without any treatment. The reaction equation for Example 1 is as follows Figure 1 shown.
[0057] The functionalized oligomer has a number average molecular weight of 5.5 kDa, a molecular weight distribution of 3.33, a functionality of 0.66 mol%, a carboxyl content of 43.8%, a carbonyl content of 56.2%, a hydroxyl content of 0%, a melting point of 122.5° C., and a crystallinity of 51.3%.
[0058] Example 2
[0059] The experimental conditions are: reaction time is 2 hours, and other experimental conditions are the same as Example 1. The number average molecular weight is 3.4 kDa, the molecular weight distribution is 2.91, the functionality is 3.29 mol%, the carboxyl content is 34.4%, the carbonyl content is 45.9%, the hydroxyl content is 19.7%, the melting point is 118.0°C, and the crystallinity is 51.4%.
[0060] Example 3
[0061] The experimental conditions are: reaction time is 6 hours, and other experimental conditions are the same as Example 1. The number average molecular weight is 1.5 kDa, the molecular weight distribution is 3.23, the functionality is 4.80 mol%, the carboxyl content is 35.3%, the carbonyl content is 47.4%, the hydroxyl content is 17.3%, the melting point is 106.5°C, and the crystallinity is 49.0%.
[0062] Example 4
[0063] The experimental conditions are: reaction time is 12 hours, and other experimental conditions are the same as Example 1. The number average molecular weight is 1.5 kDa, the molecular weight distribution is 3.25, the functionality is 5.50 mol%, the carboxyl content is 40.4%, the carbonyl content is 47.8%, the hydroxyl content is 11.8%, the melting point is 104.5°C, and the crystallinity is 50.2%.
[0064] The functionalized oligomers prepared in Examples 1-4 were characterized, and the characterization results are shown in Table 1. The oxidative pyrolysis technology scheme of the present invention can achieve adjustable molecular weight and molecular weight distribution of the pyrolysis product. Figure 2 It is a schematic diagram of the mass fraction of the functionalized oligomers of Examples 1-4. It can be seen that the reaction time can affect the molecular weight of the functionalized oligomers. The longer the reaction time, the more accumulated β-fracture events, which is reflected in the lower molecular weight of the product. At the same time, oxygen-containing groups such as carboxyl, carbonyl, and hydroxyl can be introduced while the retired polyolefin chain is broken, thereby successfully preparing the functionalized oligomers.
[0065] Table 1: Characterization results of functionalized oligomers
[0066]
[0067] Example 5
[0068] In this embodiment, the functionalized oligomer is selected from the functionalized oligomer obtained in Example 4, the epoxidized rubber is selected from epoxidized cis-1,4-dimethyl imidazole, the epoxidation rate is selected from 8 mol%, the catalyst is selected from 1,2-dimethyl imidazole, and the solvent is selected from toluene. Before the experiment, the epoxidized cis-1,4-dimethyl imidazole, the functionalized oligomer obtained in Example 4, and the 1,2-dimethyl imidazole are mixed in a ratio of 1:0.09:0.03, and placed in a glass container, and the solvent toluene is added to the glass container to maintain the overall concentration of 0.05 g / ml. The glass container is raised to 90°C, stirred at 500 rpm, and stirred for 15 minutes before mixing. The solid mixture of the solvent toluene is removed, and the solid mixture is placed on a flat vulcanizer for cross-linking reaction, the vulcanization temperature is 150°C, the vulcanization pressure is 10MPa, and the vulcanization time is 30 minutes. After cross-linking, the elastomeric material of the present invention is obtained, which has good mechanical properties and thermomechanical properties.
[0069] Example 6
[0070] The experimental conditions are as follows: the experimental material ratio is changed to 1:0.23:0.03, and the other experimental conditions are the same as those in Example 5. The obtained elastomeric material has good mechanical properties and thermomechanical properties.
[0071] Example 7
[0072] The experimental conditions are as follows: the experimental material ratio is changed to 1:0.33:0.03, and the other experimental conditions are the same as those in Example 5. The obtained elastomeric material has good mechanical properties and thermomechanical properties.
[0073] Example 8
[0074] The experimental conditions are as follows: the experimental material ratio is changed to 1:0.5:0.03, and the other experimental conditions are the same as those in Example 5. The obtained elastomeric material has good mechanical properties and thermomechanical properties.
[0075] The elastomers prepared in the above Examples 5-8 were tested, and the test results are shown in Table 2. The functionalized oligomer prepared by the oxidative cracking technology scheme of the present invention can further undergo a dynamic crosslinking reaction with the epoxidized rubber to synergistically construct an elastomer material, which has both physical crosslinking points and dynamic crosslinking points, so that the material has excellent mechanical properties and thermomechanical properties. Figure 3 is a stress-strain schematic diagram of Examples 5 to 8, and it can be seen that the content of the functionalized oligomer affects the mechanical properties of the elastomeric material; Figure 4 3 is a curve diagram showing the change of storage modulus with temperature in Examples 5 to 8. It can be seen that the content of the functionalized oligomer affects the thermomechanical properties of the elastomeric material.
[0076] At the same time, the dynamic cross-linking points give the elastomer material the functional characteristics of being reprocessable.
[0077] Table 2: Elastomer material performance results
[0078]
[0079]
[0080] The present invention is not limited to the above-mentioned optimal implementation mode. Anyone can derive other various forms of products under the inspiration of the present invention. However, no matter what changes are made in the shape or structure, all technical solutions that are the same or similar to those of the present application fall within the protection scope of the present invention.
Claims
1. A method for preparing functionalized oligomers based on oxidative cracking of retired polyolefins, characterized in that: The following steps are involved: dissolving an aerobic oxidation catalyst and retired polyolefin in an organic solvent at a certain mass ratio and transferring the dissolved catalyst and retired polyolefin into a reactor; An oxidant gas is introduced into the reactor until it is sealed, the reaction temperature of the reactor is adjusted to a high temperature state, and the reaction is stirred for a period of time to obtain a precipitated material, wherein the oxidant gas and the retired polyolefin undergo a free radical oxidation reaction under the action of an aerobic oxidation catalyst to generate free radicals, and the free radicals are used to break the retired polyolefin and introduce functional groups; The precipitation material is dissolved to obtain a reaction precipitation solution, the reaction precipitation solution is filtered to obtain a precipitation solid, and the precipitation solid is dried to obtain a functionalized oligomer.
2. The method for preparing functionalized oligomers based on oxidative cracking of retired polyolefins according to claim 1, characterized in that: The aerobic oxidation catalyst is selected from one or more of N-hydroxyphthalimide, N-hydroxysuccinimide, N-hydroxymaleimide, N-acetylphthalimide, 3,4,5,6-tetrachloro-N-hydroxyphthalimide, 3,4,5,6-tetrabromo-N-hydroxyphthalimide, 3,4,5,6-tetrafluoro-N-hydroxyphthalimide, 2,2,6,6-tetramethylpiperidinoxide, N,N'-dihydroxyphthalimide, N,N',N"-trihydroxyisocyanuric acid, 2-azaadamantane-N-oxy, N-hydroxy-3,4,5,6-tetraphenylphthalimide, N,N'-dihydroxypyromellitic acid imide, and N-hydroxyquinoline imide, and mixed in any proportion.
3. The method for preparing functionalized oligomers based on oxidative cracking of retired polyolefins according to claim 1, characterized in that: The retired polyolefin is one or more of low-density polyethylene, high-density polyethylene, linear low-density polyethylene, isotactic polypropylene, syndiotactic polypropylene, random polypropylene, polystyrene, ethylene and α-olefin copolymer mixed in any proportion.
4. The method for preparing functionalized oligomers based on oxidative cracking of retired polyolefins according to claim 1, characterized in that: The oxidant gas is one or more of air, oxygen, ozone, nitrogen dioxide and nitric oxide mixed in any proportion.
5. The method for preparing functionalized oligomers based on oxidative cracking of retired polyolefins according to claim 1, characterized in that: The mass ratio of the aerobic oxidation catalyst to the retired polyolefin is 1-100:100-1.
6. The method for preparing functionalized oligomers based on oxidative cracking of retired polyolefins according to claim 1, characterized in that: The pressure of the oxidant gas is 1 to 30 bar.
7. The method for preparing functionalized oligomers based on oxidative cracking of retired polyolefins according to claim 1, characterized in that: The reaction temperature of the reactor is adjusted to 90° C. to 130° C., and the reaction is stirred for 1 h to 48 h to obtain a precipitated material.
8. The method for preparing functionalized oligomers based on oxidative cracking of retired polyolefins according to claim 1, characterized in that: The number average molecular weight of the functionalized oligomers is 1500–10000 Da, the molecular weight distribution index is 2.0–4.0, the crystallinity is 30–60%, the functionality relative to ethylene monomer is 0.5–6.0 mol% (relative to ethylene monomer), and the selectivity of the functionalized groups is 0–50%.
9. An application method of functionalized oligomers based on oxidative cracking of retired polyolefins, characterized in that: The following steps are involved: Mixing epoxidized rubber, functionalized oligomer and catalyst in a certain mass ratio to obtain a mixture, and premixing the mixture in an organic solvent and stirring and reacting at high temperature for a period of time, wherein the functionalized oligomer is prepared according to any one of claims 1 to 7, based on the functionalized oligomer of retired polyolefin oxidative cracking; The organic solvent is removed to obtain a solid mixture, and the solid mixture is placed on a flat vulcanizer to undergo a vulcanization and cross-linking reaction to obtain an elastomeric material.
10. The application method of the functionalized oligomer based on oxidative cracking of retired polyolefins according to claim 9, characterized in that: The cross-linked network of the elastomeric material has dynamic chemical cross-linking points and physical cross-linking points, wherein the dynamic chemical cross-linking points are provided by new bonds and new groups formed between the oxidized groups of the functionalized oligomers and the epoxy groups in the epoxidized rubber, and the physical cross-linking points are provided by the semi-crystalline regions of the functionalized oligomers.
Citation Information
Patent Citations
Terminal-modified conjugated diene-based polymer, rubber composition, and rubber article
CN109071685A
Polyolefin carbonization method
CN110817840A
Functionalized liquid regenerated rubber and preparation method thereof
CN113248784A
Preparation method of polyolefin thermoplastic elastomer based on dynamic crosslinking modification
CN113896998A
Method for preparing light oil from retired polyolefin through low-temperature catalytic hydrogenolysis of two-dimensional nanosheets
CN115725318A